Variation in Platelet Transfusion Practices in Cardiac Surgery. Issue 2 (March 2019) - Zhou, Xun; Fraser, Charles D.; Suarez-Pierre, Alejandro; Crawford, Todd C.; Alejo, Diane; Conte, John V.; Lawton, Jennifer S.; Fonner, Clifford E.; Taylor, Bradley S.; Whitman, Glenn J.R.; Salenger, Rawn
Abstract : Objective: Although the morbidity associated with red blood cell transfusion in cardiac surgery has been well described, the impacts of platelet transfusion are less clearly understood. Given the conflicting results of prior studies, we sought to investigate the impact of platelet transfusion on outcomes after cardiac surgery across institutions in Maryland. Methods: Using a multiinstitutional statewide database created by the Maryland Cardiac Surgery Quality Initiative, we retrospectively analyzed data from 10, 478 patients undergoing isolated coronary artery bypass across 10 centers. Platelet transfusion practices were compared between institutions. Multivariate logistic regression model was used to analyze the association between platelet transfusion and 30-day mortality and postoperative complications. Results: Rates of platelet transfusion varied between institutions from 4.4% to 24.7% ( P < 0.001), a difference that remained statistically significant in propensity score–matched cohorts. Among patients on preoperative antiplatelet therapy, transfusion rates varied from 8.5% to 46.4% ( P < 0.001). There was no statistically significant relationship between case volume and transfusion rates ( P = 0.815). In multivariate logistic regression, platelet transfusion was associated with increased risk of 30-day mortality (OR 2.43, P = 0.008), postoperative pneumonia (OR 2.21, P = 0.004), prolonged intubation (OR 2.05, P < 0.001), and readmission (OR 1.43, P = 0.039). Conclusions: Significant variation existed in platelet transfusion rates between institutions, even after controlling for various risk factors. This variation may be associated with increased mortality and length of stay. Further study is warranted to better understand risks associated with platelet transfusion. Standardizing practice may help reduce risk and conserve resources.